2013
DOI: 10.1165/rcmb.2011-0396oc
|View full text |Cite
|
Sign up to set email alerts
|

The Nuclear Factor Erythroid 2–Related Factor 2 Activator Oltipraz Attenuates Chronic Hypoxia–Induced Cardiopulmonary Alterations in Mice

Abstract: Nuclear factor erythroid 2-related factor 2 (Nrf2) is a key regulator that activates many antioxidant enzymes. Oxidative stress, which accumulates in diseased lungs associated with pulmonary hypertension (PH), is thought to be responsible for the progression of cardiopulmonary changes. To test whether Nrf2 activation would exert therapeutic efficacy against cardiopulmonary changes in a hypoxia-induced PH model, wild-type (WT) and Nrf2-deficient mice as well as Kelch-like ECH associating protein 1 (Keap1) (nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 47 publications
1
40
0
Order By: Relevance
“…Third, Bsg +/-VSMCs exhibited increased expression of nuclear factor E2-related factor-2 and heme oxygenase-1, which inhibit hypoxia-induced PH. 40,41 Consistently, in Bsg +/-VSMCs, proliferation of VSMCs was inhibited and integrin expression and secretion of growth factors were also inhibited in response to extracellular CyPA and hypoxia. Thus, extracellular CyPA and vascular Bsg cooperatively stimulate recruitment of inflammatory cells to the vessel wall, exacerbating perivascular inflammation and VSMC proliferation.…”
Section: Vascular Bsg Regulates Pulmonary Vascular Remodelingmentioning
confidence: 80%
“…Third, Bsg +/-VSMCs exhibited increased expression of nuclear factor E2-related factor-2 and heme oxygenase-1, which inhibit hypoxia-induced PH. 40,41 Consistently, in Bsg +/-VSMCs, proliferation of VSMCs was inhibited and integrin expression and secretion of growth factors were also inhibited in response to extracellular CyPA and hypoxia. Thus, extracellular CyPA and vascular Bsg cooperatively stimulate recruitment of inflammatory cells to the vessel wall, exacerbating perivascular inflammation and VSMC proliferation.…”
Section: Vascular Bsg Regulates Pulmonary Vascular Remodelingmentioning
confidence: 80%
“…Moreover, recent studies have shown that the NRF2 activators such as UDCA and oltipraz induced MRP efflux transporters in rodent liver (Eba et al, 2013;Okada et al, 2008;Weerachayaphorn et al, 2014), and NRF2 binds to AREs at -9919 bp in the mouse MRP3 gene and to AREs/antioxidant response-like elements a t -3753 to -3767 bp in the mouse MRP4 gene (Maher et al, 2007). In this study, BDL caused intrinsic activation of NRF2 in mice as an adaptive response, however, this adaption was not potent in fully preventing cholestatic liver injury as demonstrated by marked liver pathological alteration and upregulation of multiple serum and liver biochemicals.…”
Section: Discussionmentioning
confidence: 99%
“…Heme interacts directly with Bach1, a transcriptional repressor, to deactivate it and allow for transcription of a multitude of genes in the metabolism of heme, including HO-1 (71). An additional mechanism includes heme-mediated stabilization of the transcription factor NF-E2-related factor 2 (Nrf2), a potent regulator of antioxidant proteins for which there is experimental evidence suggesting a protective effect in pulmonary vascular disease (72). This tightly regulated program likely serves as a protective mechanism in periods of high oxidant stress.…”
Section: Iron and Oxidative Stressmentioning
confidence: 99%